From Two-Eyed to Three-Eyed Seeing: A Third Space Beyond Binaries - Cathy Richardson Kineweskwêw (Murmurations)
As a Métis therapist and academic, it is not unusual for me to write from the margins. I live on land that is referred to, by Indigenous people, as (northern) Turtle Island, aka Canada. Referring to this land by one of its Indigenous names means that we situate this space apart from the dominant, British and French colonized society. We project our Indigenous inner landscape (ways of knowing and being) onto the landscape and fortify our Indigenous inner world with reinforcing experiences of interacting with the social and natural world. As Métis people, I believe we try to also call forth a Métis space in which we can dwell, a virtual “road allowance”. In this space, we can laugh and cry together, scheme, strategize, and grieve (Richardson, 2006; Troupe and Gaudet, 2024). This article explores the “third space” and what it means for Métis people to live across multiple spaces and to resist notions of “pure race” and other forms of colonial claptrap.